Preparation method of phenolic resin / sucrose-based hard carbon material and material

Through the preparation method of phenolic resin and sucrose-based hard carbon material, a nanosphere stacked structure is formed, which solves the problem of insufficient performance of the negative electrode material of traditional sodium ion battery, and achieves efficient sodium storage performance and capacity retention, which is suitable for industrial production.

CN119118108AInactive Publication Date: 2024-12-13BEIFANG UNIV OF NATITIES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411256853.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional sodium ion battery negative electrode materials have slow kinetic performance, short service life, and low safety performance. When a single phenolic resin or sucrose pyrolytic carbon is used as an electrode material, the first time Coulomb efficiency, low capacity and fast capacity decay, which cannot realize the industry. change.

Method used

The preparation method of phenolic resin and sucrose-based hard carbon material is adopted to form a nanosphere stacked structure through solvothermal reaction, grinding, preoxidation and carbonization treatment, and improve the structural stability and electrochemical properties of the material.

Benefits of technology

It significantly improves the sodium storage performance and capacity retention rate of the negative electrode material of sodium ion battery, and the first Coulomb efficiency reaches 77.4%, and reduces the energy consumption of the material preparation process, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118108A_ABST
    Figure CN119118108A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field, and provides a phenolic resin / sucrose-based hard carbon material preparation method and material.The phenolic resin / sucrose-based hard carbon material preparation method comprises the steps that phenolic resin and N, N-dimethylformamide are adopted according to the proportion to prepare a solution A, sucrose, hexamethylenetetramine and deionized water are adopted according to the proportion to prepare a solution B, and the solution B is prepared into a phenolic resin / sucrose-based hard carbon material; adding the solution B into the solution A according to the proportion to prepare a phenolic resin / sucrose-based hard carbon precursor solution; placing the prepared phenolic resin / sucrose-based hard carbon precursor solution in a reaction kettle for solvothermal reaction, and cleaning and drying a solvothermal reaction product to prepare a phenolic resin / sucrose-based hard carbon precursor; grinding the prepared phenolic resin / sucrose-based hard carbon precursor, carrying out pre-oxidation treatment on a grinding product, and carrying out carbonization treatment on a product subjected to the pre-oxidation treatment, so as to prepare the phenolic resin / sucrose-based hard carbon material. The phenolic resin / sucrose-based hard carbon material with stable structure and excellent electrochemical performance can be efficiently prepared at low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field, and in particular to a preparation method and material of a phenolic resin / sucrose-based hard carbon material. Background Art

[0002] Sodium-ion batteries have great development prospects in the future new energy vehicle battery applications and energy storage fields due to their wide range of raw materials and low cost. Traditional electrode materials have slow kinetic performance, short service life and low safety performance in the application of sodium-ion batteries. Therefore, developing negative electrode materials suitable for sodium-ion batteries is one of the important ways to improve the performance of sodium-ion batteries.

[0003] At present, the research on negative electrode materials for sodium ion batteries mainly includes carbon-based materials, alloy materials, transition metal oxides and organic compounds. Among them, carbon-based materials are favored due to their high sodium storage platform, high capacity, long cycle life, low price and small volume expansion. Traditional electrode carbon materials have appropriate interlayer spacing, stable structure and are environmentally friendly materials. Hard carbon precursors are rich in sources, including resins, polymers, process waste, biomass, etc. Hard carbon has a high low-voltage platform capacity as a negative electrode material for sodium ion batteries and is one of the most promising negative electrode materials for sodium ion batteries. Phenolic resin and sucrose are hard carbon precursors, which have the advantages of stable properties, relatively low price and high carbon yield. However, when a single phenolic resin or pyrolysis carbon of sucrose is used as an electrode material, the first coulomb efficiency is low, the capacity is low and the capacity decays quickly, so it cannot be industrialized. Therefore, it is necessary to improve the synthesis method of the material. Many researchers have studied phenolic resin and sucrose-based hard carbon materials. On the one hand, metal doping is performed on carbon materials to increase the active sites of electrochemical reactions, thereby improving the electrochemical performance of the materials. On the other hand, the carbonization process is improved and the carbonization temperature is optimized to improve the structural stability of the carbon materials, so as to achieve the purpose of improving their electrochemical performance as negative electrode materials for sodium ion batteries. However, screening suitable hard carbon precursors and optimizing the carbonization temperature are still a huge challenge.

[0004] Therefore, how to develop an efficient synthesis method for hard carbon sodium ion battery negative electrode materials, which not only takes advantage of the high yield of phenolic resin and sucrose charcoal, but also ensures that it has a high reversible capacity and capacity retention rate, has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of this, in order to overcome the deficiencies of the prior art, the present invention aims to provide a preparation method and material of a phenolic resin / sucrose-based hard carbon material.

[0006] According to a first aspect of the present invention, there is provided a method for preparing a phenolic resin / sucrose-based hard carbon material, the method comprising:

[0007] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0008] A solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio, a solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio, and the solution B is added to the solution A according to a ratio to prepare a phenolic resin / sucrose-based hard carbon precursor solution;

[0009] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0010] placing the prepared phenolic resin / sucrose-based hard carbon precursor solution in a reaction kettle for a solvothermal reaction, washing and drying the solvothermal reaction product to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0011] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0012] The prepared phenolic resin / sucrose-based hard carbon precursor is ground, the ground product is pre-oxidized, and the pre-oxidized product is carbonized to prepare the phenolic resin / sucrose-based hard carbon material.

[0013] Preferably, in the preparation method of the phenolic resin / sucrose-based hard carbon material of the present invention, in step one, solution A is prepared using phenolic resin and N,N-dimethylformamide in a ratio, including: using phenolic resin as a solute and N,N-dimethylformamide as a solvent to prepare solution A, wherein every 4.5 g of phenolic resin is matched with 36 mL of N,N-dimethylformamide.

[0014] Preferably, in the preparation method of the phenolic resin / sucrose-based hard carbon material of the present invention, in step one, solution B is prepared using sucrose, hexamethylenetetramine and deionized water in a ratio, including: using sucrose and hexamethylenetetramine as solutes and deionized water as solvent to prepare solution B, wherein every 4.5g of sucrose is matched with 0.09-0.9g of hexamethylenetetramine and 36mL of deionized water.

[0015] Preferably, in the preparation method of the phenolic resin / sucrose-based hard carbon material of the present invention, in step one, solution B is added to solution A according to a ratio to prepare a phenolic resin / sucrose-based hard carbon precursor solution, including: adding solution B to solution A at a volume ratio of 1:1 and stirring at room temperature for 1 hour, and before adding solution B to solution A, stirring solution B and solution A at room temperature for 0.5 hour respectively.

[0016] Preferably, in the method for preparing the phenolic resin / sucrose-based hard carbon material of the present invention, in step 2, the temperature of the solvent thermal reaction is 180-200° C., and the time of the solvent thermal reaction is 8-12 h.

[0017] Preferably, in the method for preparing the phenolic resin / sucrose-based hard carbon material of the present invention, in step 2, the solvent thermal reaction product is cleaned and dried, including: using anhydrous ethanol to clean the solvent thermal reactant, and drying the cleaned solvent thermal reactant at 100° C. for 12 hours.

[0018] Preferably, the preparation method of the phenolic resin / sucrose-based hard carbon material of the present invention grinds the prepared phenolic resin / sucrose-based hard carbon precursor, including: grinding the prepared phenolic resin / sucrose-based hard carbon precursor into a powder with an average particle size of less than 100 nm.

[0019] Preferably, in the preparation method of the phenolic resin / sucrose-based hard carbon material of the present invention, in step three, the ground product is pre-oxidized, including: heating the ground product to 150-250°C at a heating rate of 5°C / min in an air atmosphere, keeping it warm for 10-12 hours, and then naturally cooling it to room temperature.

[0020] Preferably, in the preparation method of the phenolic resin / sucrose-based hard carbon material of the present invention, in step three, the product of the pre-oxidation treatment is carbonized, including: heating the product of the pre-oxidation treatment to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping it warm for 4 hours and then naturally cooling it to room temperature.

[0021] According to a second aspect of the present invention, a phenolic resin / sucrose-based hard carbon material is provided. The phenolic resin / sucrose-based hard carbon material is prepared according to the above method.

[0022] The preparation method and material of the phenolic resin / sucrose-based hard carbon material of the present invention have the following beneficial technical effects:

[0023] 1. Utilizing the rich functional groups of sucrose and phenolic resin, the molecular structure of phenolic resin is changed and cross-linked with sucrose during the solvothermal reaction to obtain a phenolic resin / sucrose-based hard carbon precursor. While ensuring the carbon yield, the structural stability of the material is improved, thereby improving its sodium storage performance as a negative electrode material for sodium ion batteries;

[0024] 2. Through pre-oxidation treatment, the material forms a preliminary stable structure and produces a large number of favorable defects, which is helpful for the next step of carbonization treatment, greatly reduces the temperature of the subsequent carbonization treatment, and significantly reduces the energy consumption in the material preparation process;

[0025] 3. Through carbonization treatment, the residual internal stress in the material is reduced, so that the internal structure of the material presents a morphology structure with suitable interlayer spacing and composed of stacked nanospheres under high temperature, which enhances the structural uniformity and stability of the material and improves its sodium storage performance as a negative electrode material for sodium ion batteries;

[0026] 4. The phenolic resin / sucrose-based hard carbon material prepared by the present invention is composed of nanospheres of uniform size and average diameter less than 50nm stacked together. The stacked structure of the nanospheres is conducive to dispersing the internal stress generated during the charge and discharge process when it is used as a negative electrode material for sodium ion batteries, reducing volume expansion and improving the capacity retention rate of sodium ion batteries. The average interlayer spacing of the material is calculated to be It is conducive to the embedding and extraction of sodium ions and improves the transmission rate of sodium ions. When used as the negative electrode material of sodium ion batteries, its first cycle charge capacity can reach 359.24mAh / g, discharge capacity can reach 464.91mAh / g, and first coulomb efficiency can reach 77.4%, showing excellent electrochemical performance.

[0027] 5. The preparation method of the present invention has a simple and efficient process with low process energy consumption, and can be widely used in the preparation of negative electrode materials for sodium ion batteries, which is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 1 of the present invention, wherein: Figure 1 (a) The magnification is 50,000 times. Figure 1 (b) The magnification is 150,000 times;

[0030] Figure 2 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 2 of the present invention, wherein: Figure 2 (a) The magnification is 50,000 times. Figure 2 (b) The magnification is 150,000 times;

[0031] Figure 3 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 3 of the present invention, wherein: Figure 3 (a) The magnification is 50,000 times. Figure 3 (b) The magnification is 150,000 times;

[0032] Figure 4 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 4 of the present invention, wherein: Figure 4 (a) The magnification is 50,000 times. Figure 4 (b) The magnification is 150,000 times;

[0033] Figure 5 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 5 of the present invention, wherein: Figure 5 (a) The magnification is 50,000 times. Figure 5 (b) The magnification is 150,000 times;

[0034] Figure 6 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 6 of the present invention, wherein: Figure 6 (a) The magnification is 50,000 times. Figure 6 (b) The magnification is 150,000 times;

[0035] Figure 7 XRD patterns of phenolic resin / sucrose-based hard carbon materials prepared in Examples 2, 3, 4 and 5 of the present invention;

[0036] Figure 8 The rate performance diagram of the phenolic resin / sucrose-based hard carbon materials prepared in Examples 1, 2, 3, 4, 5 and 6 of the present invention;

[0037] Fig. 9 This is a charge-discharge curve diagram of the first five cycles of the phenolic resin / sucrose-based hard carbon material prepared in Example 3 of the present invention at a current density of 0.5 A / g. DETAILED DESCRIPTION

[0038] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0039] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0040] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0041] Example 1

[0042] Preparation of phenolic resin / sucrose-based hard carbon materials:

[0043] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0044] Solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio. Specifically, solution A is prepared by using phenolic resin as a solute and N,N-dimethylformamide as a solvent, wherein 4.5 g of phenolic resin is mixed with 36 mL of N,N-dimethylformamide;

[0045] Solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio. Specifically, sucrose and hexamethylenetetramine are used as solutes and deionized water is used as a solvent to prepare solution B, wherein 4.5 g of sucrose is mixed with 0.09 g of hexamethylenetetramine and 36 mL of deionized water;

[0046] The phenolic resin / sucrose-based hard carbon precursor solution was prepared by adding solution B to solution A according to the ratio. Specifically, solution B was added to solution A at a volume ratio of 1:1 and stirred at room temperature for 1 hour. Before adding solution B to solution A, solution B and solution A were stirred at room temperature for 0.5 hour respectively;

[0047] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0048] The prepared phenolic resin / sucrose-based hard carbon precursor solution was placed in a reactor for a solvothermal reaction at a temperature of 180°C and a time of 12 hours.

[0049] The solvent thermal reaction product is cleaned and dried. Specifically, the solvent thermal reaction product is cleaned with anhydrous ethanol, and the cleaned solvent thermal reaction product is dried at 100° C. for 12 hours to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0050] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0051] The prepared phenolic resin / sucrose-based hard carbon precursor is ground into powder with an average particle size of less than 100 nm using an agate mortar;

[0052] The ground product is subjected to a pre-oxidation treatment. Specifically, the ground product is heated to 150° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 12 hours, and then naturally cooled to room temperature;

[0053] The pre-oxidation product is carbonized, specifically, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping the temperature for 4 hours and then naturally cooling to room temperature to obtain a phenolic resin / sucrose-based hard carbon material.

[0054] Example 2

[0055] Preparation of phenolic resin / sucrose-based hard carbon materials:

[0056] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0057] Solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio. Specifically, solution A is prepared by using phenolic resin as a solute and N,N-dimethylformamide as a solvent, wherein 4.5 g of phenolic resin is mixed with 36 mL of N,N-dimethylformamide;

[0058] Solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio. Specifically, sucrose and hexamethylenetetramine are used as solutes and deionized water is used as a solvent to prepare solution B, wherein 4.5 g of sucrose is mixed with 0.9 g of hexamethylenetetramine and 36 mL of deionized water;

[0059] The phenolic resin / sucrose-based hard carbon precursor solution was prepared by adding solution B to solution A according to the ratio. Specifically, solution B was added to solution A at a volume ratio of 1:1 and stirred at room temperature for 1 hour. Before adding solution B to solution A, solution B and solution A were stirred at room temperature for 0.5 hour respectively;

[0060] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0061] The prepared phenolic resin / sucrose-based hard carbon precursor solution was placed in a reactor for a solvothermal reaction at a temperature of 180°C and a time of 12 hours.

[0062] The solvent thermal reaction product is cleaned and dried. Specifically, the solvent thermal reaction product is cleaned with anhydrous ethanol, and the cleaned solvent thermal reaction product is dried at 100° C. for 12 hours to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0063] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0064] The prepared phenolic resin / sucrose-based hard carbon precursor is ground into powder with an average particle size of less than 100 nm using an agate mortar;

[0065] The ground product is subjected to a pre-oxidation treatment. Specifically, the ground product is heated to 200° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 11 hours, and then naturally cooled to room temperature;

[0066] The pre-oxidation product is carbonized, specifically, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping the temperature for 4 hours and then naturally cooling to room temperature to obtain a phenolic resin / sucrose-based hard carbon material.

[0067] Example 3

[0068] Preparation of phenolic resin / sucrose-based hard carbon materials:

[0069] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0070] Solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio. Specifically, solution A is prepared by using phenolic resin as a solute and N,N-dimethylformamide as a solvent, wherein 4.5 g of phenolic resin is mixed with 36 mL of N,N-dimethylformamide;

[0071] Solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio. Specifically, sucrose and hexamethylenetetramine are used as solutes and deionized water is used as a solvent to prepare solution B, wherein 4.5 g of sucrose is mixed with 0.27 g of hexamethylenetetramine and 36 mL of deionized water;

[0072] The phenolic resin / sucrose-based hard carbon precursor solution was prepared by adding solution B to solution A according to the ratio. Specifically, solution B was added to solution A at a volume ratio of 1:1 and stirred at room temperature for 1 hour. Before adding solution B to solution A, solution B and solution A were stirred at room temperature for 0.5 hour respectively;

[0073] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0074] The prepared phenolic resin / sucrose-based hard carbon precursor solution was placed in a reactor for a solvothermal reaction at a temperature of 180°C and a time of 12 hours.

[0075] The solvent thermal reaction product is cleaned and dried. Specifically, the solvent thermal reaction product is cleaned with anhydrous ethanol, and the cleaned solvent thermal reaction product is dried at 100° C. for 12 hours to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0076] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0077] The prepared phenolic resin / sucrose-based hard carbon precursor is ground into powder with an average particle size of less than 100 nm using an agate mortar;

[0078] The ground product is subjected to a pre-oxidation treatment. Specifically, the ground product is heated to 250° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 10 hours, and then naturally cooled to room temperature;

[0079] The pre-oxidation product is carbonized, specifically, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping the temperature for 4 hours and then naturally cooling to room temperature to obtain a phenolic resin / sucrose-based hard carbon material.

[0080] Example 4

[0081] Preparation of phenolic resin / sucrose-based hard carbon materials:

[0082] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0083] Solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio. Specifically, solution A is prepared by using phenolic resin as a solute and N,N-dimethylformamide as a solvent, wherein 4.5 g of phenolic resin is mixed with 36 mL of N,N-dimethylformamide;

[0084] Solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio. Specifically, sucrose and hexamethylenetetramine are used as solutes and deionized water is used as a solvent to prepare solution B, wherein 4.5 g of sucrose is mixed with 0.63 g of hexamethylenetetramine and 36 mL of deionized water;

[0085] The phenolic resin / sucrose-based hard carbon precursor solution was prepared by adding solution B to solution A according to the ratio. Specifically, solution B was added to solution A at a volume ratio of 1:1 and stirred at room temperature for 1 hour. Before adding solution B to solution A, solution B and solution A were stirred at room temperature for 0.5 hour respectively;

[0086] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0087] The prepared phenolic resin / sucrose-based hard carbon precursor solution was placed in a reactor for a solvothermal reaction at a temperature of 180°C and a time of 12 hours.

[0088] The solvent thermal reaction product is cleaned and dried. Specifically, the solvent thermal reaction product is cleaned with anhydrous ethanol, and the cleaned solvent thermal reaction product is dried at 100° C. for 12 hours to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0089] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0090] The prepared phenolic resin / sucrose-based hard carbon precursor is ground into powder with an average particle size of less than 100 nm using an agate mortar;

[0091] The ground product is subjected to a pre-oxidation treatment. Specifically, the ground product is heated to 150° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 10 hours, and then naturally cooled to room temperature;

[0092] The pre-oxidation product is carbonized, specifically, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping the temperature for 4 hours and then naturally cooling to room temperature to obtain a phenolic resin / sucrose-based hard carbon material.

[0093] Example 5

[0094] Preparation of phenolic resin / sucrose-based hard carbon materials:

[0095] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0096] Solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio. Specifically, solution A is prepared by using phenolic resin as a solute and N,N-dimethylformamide as a solvent, wherein 4.5 g of phenolic resin is mixed with 36 mL of N,N-dimethylformamide;

[0097] Solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio. Specifically, sucrose and hexamethylenetetramine are used as solutes and deionized water is used as a solvent to prepare solution B, wherein 4.5 g of sucrose is mixed with 0.09 g of hexamethylenetetramine and 36 mL of deionized water;

[0098] The phenolic resin / sucrose-based hard carbon precursor solution was prepared by adding solution B to solution A according to the ratio. Specifically, solution B was added to solution A at a volume ratio of 1:1 and stirred at room temperature for 1 hour. Before adding solution B to solution A, solution B and solution A were stirred at room temperature for 0.5 hour respectively;

[0099] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0100] The prepared phenolic resin / sucrose-based hard carbon precursor solution was placed in a reactor for a solvothermal reaction at a temperature of 200°C and a time of 8 hours.

[0101] The solvent thermal reaction product is cleaned and dried. Specifically, the solvent thermal reaction product is cleaned with anhydrous ethanol, and the cleaned solvent thermal reaction product is dried at 100° C. for 12 hours to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0102] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0103] The prepared phenolic resin / sucrose-based hard carbon precursor is ground into powder with an average particle size of less than 100 nm using an agate mortar;

[0104] The ground product is subjected to a pre-oxidation treatment. Specifically, the ground product is heated to 150° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 10 hours, and then naturally cooled to room temperature;

[0105] The pre-oxidation product is carbonized, specifically, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping the temperature for 4 hours and then naturally cooling to room temperature to obtain a phenolic resin / sucrose-based hard carbon material.

[0106] Example 6

[0107] Preparation of phenolic resin / sucrose-based hard carbon materials:

[0108] Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution

[0109] Solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio. Specifically, solution A is prepared by using phenolic resin as a solute and N,N-dimethylformamide as a solvent, wherein 4.5 g of phenolic resin is mixed with 36 mL of N,N-dimethylformamide;

[0110] Solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio. Specifically, sucrose and hexamethylenetetramine are used as solutes and deionized water is used as a solvent to prepare solution B, wherein 4.5 g of sucrose is mixed with 0.09 g of hexamethylenetetramine and 36 mL of deionized water;

[0111] The phenolic resin / sucrose-based hard carbon precursor solution was prepared by adding solution B to solution A according to the ratio. Specifically, solution B was added to solution A at a volume ratio of 1:1 and stirred at room temperature for 1 hour. Before adding solution B to solution A, solution B and solution A were stirred at room temperature for 0.5 hour respectively;

[0112] Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor

[0113] The prepared phenolic resin / sucrose-based hard carbon precursor solution was placed in a reactor for a solvothermal reaction at a temperature of 190°C and a solvothermal reaction time of 10 h.

[0114] The solvent thermal reaction product is cleaned and dried. Specifically, the solvent thermal reaction product is cleaned with anhydrous ethanol, and the cleaned solvent thermal reaction product is dried at 100° C. for 12 hours to obtain a phenolic resin / sucrose-based hard carbon precursor;

[0115] Step 3: Preparation of phenolic resin / sucrose-based hard carbon material

[0116] The prepared phenolic resin / sucrose-based hard carbon precursor is ground into powder with an average particle size of less than 100 nm using an agate mortar;

[0117] The ground product is subjected to a pre-oxidation treatment. Specifically, the ground product is heated to 150° C. at a heating rate of 5° C. / min in an air atmosphere, kept at this temperature for 10 hours, and then naturally cooled to room temperature;

[0118] The pre-oxidation product is carbonized, specifically, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900°C at a heating rate of 5°C / min in an argon atmosphere, keeping the temperature for 4 hours and then naturally cooling to room temperature to obtain a phenolic resin / sucrose-based hard carbon material.

[0119] Example 7

[0120] The microstructures of the phenolic resin / sucrose-based hard carbon materials prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 were observed using a thermal field emission scanning electron microscope (FESEM) of model SIGMA 500 produced by Zeiss, Germany. The microstructures of the phenolic resin / sucrose-based hard carbon materials prepared in Examples 1 to 6 are shown in FIG. Figures 1 to 6 The experimental process and test parameters include: dispersing the material evenly on the conductive glue, sticking it on the sample stage and observing it with the instrument, and the acceleration voltage is 5kV.

[0121] Figure 1This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 1 of the present invention, wherein: Figure 1 (a) The magnification is 50,000 times. Figure 1 (b) The magnification is 150,000 times. Figure 1 As shown, the phenolic resin / sucrose-based hard carbon material prepared in Example 1 has a uniform microscopic morphology and is composed of stacked nanospheres with an average diameter of less than 50 nm. The nanospheres are evenly stacked together, which is beneficial to improving its structural stability as a negative electrode material for a sodium ion battery during the charge and discharge process, and reducing the volume expansion during the charge and discharge process, and can improve the capacity retention rate of the sodium ion battery.

[0122] Figure 2 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 2 of the present invention, wherein: Figure 2 (a) The magnification is 50,000 times. Figure 2 (b) The magnification is 150,000 times. Figure 2 As shown, the phenolic resin / sucrose-based hard carbon material prepared in Example 2 is composed of stacked nanospheres with an average diameter of less than 50 nm. The stacked structure is more stable than single nanospheres, which can buffer the internal stress generated during the charging and discharging process of the negative electrode material for sodium ion batteries, thereby reducing the volume expansion of the material and improving its cycle stability as a negative electrode material for sodium ion batteries.

[0123] Figure 3 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 3 of the present invention, wherein: Figure 3 (a) The magnification is 50,000 times. Figure 3 (b) The magnification is 150,000 times; Figure 3 As shown, the phenolic resin / sucrose-based hard carbon material prepared in Example 3 has a more uniform morphology, the nanospheres are regularly stacked and arranged, and the average diameter is less than 50 nm. Such a morphology has a more suitable specific surface area, which is beneficial to improving its first coulombic efficiency when used as a negative electrode material for a sodium ion battery and maintaining a relatively high reversible capacity.

[0124] Figure 4 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 4 of the present invention, wherein: Figure 4 (a) The magnification is 50,000 times. Figure 4 (b) The magnification is 150,000 times; Figure 4 As shown, the phenolic resin / sucrose-based hard carbon material prepared in Example 4 is composed of stacked nanospheres, the nanospheres are evenly distributed, the average diameter is less than 50 nm, and the nanospheres are stacked and arranged regularly, which is beneficial to dispersing the internal stress generated during the charge and discharge process when it is used as a negative electrode material for a sodium ion battery, thereby reducing volume expansion and improving the capacity retention rate of the sodium ion battery.

[0125] Figure 5 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 5 of the present invention, wherein: Figure 5 (a) The magnification is 50,000 times. Figure 5 (b) The magnification is 150,000 times; Figure 5 As shown, the phenolic resin / sucrose-based hard carbon material prepared in Example 5 is composed of nanospheres stacked on each other. The nanospheres are uniform in size, and their average diameter is less than 50 nm. The stacked nanospheres can act as buffers for each other, thereby improving the structural stability when used as a negative electrode material for a sodium ion battery and improving the reversible capacity of the sodium ion battery.

[0126] Figure 6 This is a FESEM image of the phenolic resin / sucrose-based hard carbon material prepared in Example 6 of the present invention, wherein: Figure 6 (a) The magnification is 50,000 times. Figure 6 (b) The magnification is 150,000 times; Figure 6 As shown, the phenolic resin / sucrose-based hard carbon material prepared in Example 6 is composed of stacked nanospheres with an average diameter of less than 50 nm, and has an appropriate specific surface area, which can enable the material to generate a stable SEI film during the first charge and discharge process when used as a negative electrode material for a sodium ion battery, thereby improving the electrochemical performance of the sodium ion battery.

[0127] Combined with the material preparation parameters of each embodiment, when the pre-oxidation temperature gradually increases from 150°C to 250°C, the morphology distribution of the material is more uniform, and the overall morphology presents a stacked morphology of nanospheres. Such morphology is more stable than that of a single nanosphere and has a suitable specific surface area, which can effectively reduce its volume expansion during the charging and discharging process when used as a negative electrode material for sodium ion batteries, thereby improving the first coulombic efficiency and cycle stability of the material.

[0128] Example 8

[0129] The physical composition of the phenolic resin / sucrose-based hard carbon materials prepared in Example 2, Example 3, Example 4, and Example 5 was analyzed using an X-ray diffractometer (XRD) of model XRD-6000 (3KW) produced by Shimadzu Corporation of Japan; the test process and test parameter settings include: placing the material in a groove (2.0*2.0cm) on a glass slide, preferably to fill the groove, and then placing it in an X-ray diffractometer, with a ray source of Cu target Kα ray (λ=0.15418nm), a scanning range of 5-80°, a scanning rate of 5° / min, a tube voltage of 40kV, and a tube current of 30mA. The test results are shown in Figure 7 .

[0130] Figure 7The XRD patterns of the phenolic resin / sucrose-based hard carbon materials prepared in Examples 2, 3, 4 and 5 of the present invention are as follows; Figure 7 As shown, all embodiments have clear diffraction peaks at 24° and 43°, corresponding to the (002) and (100) crystal planes of the carbon material, respectively, showing a disordered amorphous structure, wherein the diffraction peak intensity of each embodiment at 43° is basically the same. The diffraction peak intensity of embodiment 2 at 24° and 43° is stronger than that of other embodiments, and its corresponding interlayer spacing is 3.796, which is also smaller than that of other embodiments. Such an interlayer spacing is more conducive to the insertion and extraction of sodium ions. The diffraction peak positions and diffraction peak intensities of the remaining embodiments are relatively close, and their average interlayer spacing (d 002) is calculated to be approximately Such an interlayer spacing is more conducive to the embedding and extraction of sodium ions, thereby improving the transport efficiency of sodium ions and further improving the electrochemical performance of the material as a negative electrode material for sodium ion batteries.

[0131] Example 9

[0132] The phenolic resin / sucrose-based hard carbon material in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 were uniformly mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1 and dissolved in 1-methyl-2-pyrrolidine (NMP) to form a slurry, which was then coated on a copper foil current collector and dried in a vacuum drying oven at 60°C for 24 hours. The phenolic resin / sucrose-based hard carbon material electrode material prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 was cut into pieces using a tablet press machine of model SZ-50-14 produced by Shenzhen Kejing Material Technology Co., Ltd. The test process and test parameters include: the materials prepared in each comparative example and each example were cut into discs with a diameter of 12 mm as electrode materials for standby use, and a CR2025 battery shell, 1M NaCF3SO3 in DIGLYME (100%) electrolyte, a glass fiber separator, and a metal sodium sheet were put into a glove box with a water and oxygen content of less than 0.1 ppm to assemble the battery. After the assembled battery was left to rest for 12 hours, the electrochemical performance test was performed.

[0133] The half-cells assembled from the phenolic resin / sucrose-based hard carbon materials prepared in Examples 1, 2, 3, 4, 5, and 6 were electrochemically tested using a Blue Electric Battery Test System model CT3002A produced by Wuhan Blue Electric Electronics Co., Ltd. The test process and test parameters included: taking current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1.0 A / g, 2.0 A / g, 5.0 A / g, 10.0 A / g, and 0.1 A / g, respectively, to compare the electrochemical performance of each example through constant current charge and discharge tests, such as Figure 8 shown.

[0134] Figure 8 The rate performance diagram of the phenolic resin / sucrose-based hard carbon material prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 of the present invention; Figure 8 As shown, the charge and discharge capacity overlap of each embodiment at different current densities is high, and its efficiency is maintained at about 100%. Among them, the half-cell assembled by the phenolic resin / sucrose-based hard carbon material prepared in Example 2 and Example 4 shows good rate performance, and still has a large capacity at high current density. The half-cell assembled by the phenolic resin / sucrose-based hard carbon material prepared in Example 3 shows better rate performance, and its capacity is also higher than that of other embodiments. Its first cycle charge capacity is 359.24mAh / g, its discharge capacity is 464.91mAh / g, and its first coulombic efficiency is 77.4%. Especially at a high current density of 10.0A / g, it still has a large capacity, and its efficiency is maintained at about 99%. As the current density increases, the charge and discharge capacity of the half-cell assembled by the phenolic resin / sucrose-based hard carbon material prepared in Example 5 and Example 1 decreases very little, and the capacity at a higher current density is still objective, showing good rate performance. The remaining embodiments all have higher specific charge and discharge capacities, and higher charge and discharge capacity overlap under different current densities, and their efficiency is maintained at about 99%.

[0135] Fig. 9 The first five charge-discharge curves of the phenolic resin / sucrose-based hard carbon material prepared in Example 3 of the present invention at a current density of 0.5A / g are shown, wherein the first charge capacity is 359.24mAh / g, the discharge capacity is 464.91mAh / g, and the first coulombic efficiency is 77.4%. It has a high charge-discharge capacity, and the charge-discharge curves of the last four cycles have a high overlap, indicating that it has good charge-discharge stability, which is at a relatively high level among similar materials.

[0136] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a phenolic resin / sucrose-based hard carbon material, It is characterized in that The method comprises: Step 1: Preparation of phenolic resin / sucrose-based hard carbon precursor solution A solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio, a solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio, and the solution B is added to the solution A according to a ratio to prepare a phenolic resin / sucrose-based hard carbon precursor solution; Step 2: Preparation of phenolic resin / sucrose-based hard carbon precursor placing the prepared phenolic resin / sucrose-based hard carbon precursor solution in a reaction kettle for a solvothermal reaction, washing and drying the solvothermal reaction product to obtain a phenolic resin / sucrose-based hard carbon precursor; Step 3: Preparation of phenolic resin / sucrose-based hard carbon material The prepared phenolic resin / sucrose-based hard carbon precursor is ground, the ground product is pre-oxidized, and the pre-oxidized product is carbonized to prepare the phenolic resin / sucrose-based hard carbon material.

2. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step 1, solution A is prepared by using phenolic resin and N,N-dimethylformamide according to a ratio, including: using phenolic resin as a solute and N,N-dimethylformamide as a solvent to prepare solution A, wherein every 4.5 g of phenolic resin is matched with 36 mL of N,N-dimethylformamide.

3. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step 1, solution B is prepared by using sucrose, hexamethylenetetramine and deionized water according to a ratio, including: using sucrose and hexamethylenetetramine as solutes and deionized water as solvent to prepare solution B, wherein every 4.5 g of sucrose is mixed with 0.09-0.9 g of hexamethylenetetramine and 36 mL of deionized water.

4. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step 1, solution B is added to solution A according to a ratio to prepare a phenolic resin / sucrose-based hard carbon precursor solution, including: adding solution B to solution A at a volume ratio of 1:1 and stirring at room temperature for 1 hour, and before adding solution B to solution A, stirring solution B and solution A at room temperature for 0.5 hours respectively.

5. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step 2, the temperature of the solvent thermal reaction is 180-200° C., and the time of the solvent thermal reaction is 8-12 h.

6. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step 2, the solvent thermal reaction product is cleaned and dried, including: using anhydrous ethanol to clean the solvent thermal reaction product, and drying the cleaned solvent thermal reaction product at 100° C. for 12 hours.

7. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that The prepared phenolic resin / sucrose-based hard carbon precursor is subjected to grinding treatment, including: grinding the prepared phenolic resin / sucrose-based hard carbon precursor into powder with an average particle size of less than 100nm.

8. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step three, the ground product is pre-oxidized, including: heating the ground product to 150-250° C. at a heating rate of 5° C. / min in an air atmosphere, keeping the temperature for 10-12 hours, and then naturally cooling to room temperature.

9. The method for preparing the phenolic resin / sucrose-based hard carbon material according to claim 1, It is characterized in that In step three, the pre-oxidation product is carbonized, including: heating the pre-oxidation product to 900° C. at a heating rate of 5° C. / min in an argon atmosphere, keeping the temperature for 4 hours, and then naturally cooling to room temperature.

10. A phenolic resin / sucrose-based hard carbon material, It is characterized in that The phenolic resin / sucrose-based hard carbon material is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and modification method of hard carbon negative electrode material for lithium ion power batteries

    CN106981629A

  • Phenolic resin / sucrose-based hard carbon microsphere material, preparation method thereof and sodium ion battery

    CN112125295A

  • Hard carbon material and preparation method and application thereof

    CN114436237A

  • Preparation method and application of high-yield biomass derived carbon

    CN117438221A

  • KR20220169559A